Cardiovascular risk factors and relatedness in an Icelandic subpopulation. - Eldon, B; Axelsson, J; Sigurdsson, S; Arnason, E (2001)
Theoretical and empirical studies suggest adverse effects of inbreeding on general vigour. The genetic architecture of physiological and biochemical cardiovascular risk factors is, furthermore, an unsolved issue. Our aim with this study is to investigate potential effects of inbreeding on stated risk factors in a relatively well demarcated Icelandic subpopulation. We used genealogical records to calculate coefficient of inbreeding and estimated the potential association of the coefficient with stated risk factors with known statistical methods. The results suggest absence of inbreeding depression with exception of HDL cholesterol.